THE BAPTISM OF DEATH: READING, TODAY, THE LIFE AND DEATH OF LAKSHMI KAUNDINYA: . - Sebastian, J. Jayakiran (Journal of Dharma, 1998)
doctrine involves the utterances of speakers in the sense that doctrine is, permanently, the sign, the manifestation and the instrument of a prior adherence - adherence to a class, to a social or racial status, to a nationality or an interest, to a struggle, a revolt, resistance or acceptance. Doctrine links individuals to certain types of utterance while consequently barring them from all others. Doctrine effects a dual subjection, that of speaking subjects to discourse, and that of discourse to the group, a t least virtually, of speakers